PENERAPAN PIDANA KURUNGAN SEBAGAI PENGGANTI PIDANA DENDA TERHADAP TERPIDANA NARKOTIKA - Zainab Ompu Jainah (KEADILAN PROGRESIF, 2019)
The provision of imprisonment sanctions as a substitute for criminal fines is expected to be a solution to provide penalties and deterrent effects to prisoners who are unable orunwilling to pay fines, including narcotics convicts. The method used by the normativejuridical approach and analysis is done qualitatively. The results showed that theimplementation of imprisonment as a substitute for criminal fines against convicted narcoticsis applied to those convicted who obviously cannot afford to pay the amount of fines that havebeen determined based on court decisions that have permanent legal force. The inhibitingfactor in the implementation of imprisonment as a substitute for criminal fines againstconvicted narcotics is a system of supervision and guidance. As a suggestion, the quality andquantity of officers in monitoring and coaching needs to be improved